MUSIC VIDEO CONCEPT DESIGN WITH ARTIFICIAL INTELLIGENCE - Widiatmika, I Gusti Ngurah Bagus; Setiawan, I Nyoman Anom Fajaraditya; Wardhana, Gede Wirya (Proceeding International Conference on Information Technology, Multimedia, Architecture, Design, and E-Business, 2024)
Music, as one of the ways to express thoughts in works, has its realm of beauty. Various genres of music provide a vast space for creativity. In contemporary music, a musical creation cannot be separated from its supporters, especially to promote the artist's work. One means of media considered capable of supporting musical works is video clips. So far, the processing of video clips in their creation requires a lot of resources and devices because the majority still use conventional equipment for recording. Thanks to technological advances, an alternative has emerged, namely with the help of artificial intelligence (AI). The problem is about how to manage and the process of creating the desired output, namely video clips. In this study, the music band that was the subject was the Forever Attack band chosen to be part of the design process. In the process of using several technical supports and being dominated by AI, actual shooting is also needed to provide a more natural transition. All processes will be depicted in the scenario design and storyboard as a process guide. In the end, the design became the initial sequence in creating the video clip from the Forever Attack band, and a pre-test will be carried out as a basis for feasibility by the band's personnel.